1990
DOI: 10.1002/jts.2490030314
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic experiences in psychiatric outpatients

Abstract: Fifty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
2
5

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(71 citation statements)
references
References 19 publications
3
61
2
5
Order By: Relevance
“…Rutter [103] found that children hospitalized between six months of age and four years were more likely to have negative outcomes than those hospitalized prior to six months or after four years of age. Davidson and Smith [104] reported that among children receiving psychiatric care, those who had experienced an initial trauma prior to age ! 1 were three times as likely to develop psychiatric symptoms than those who had experienced the trauma during adolescence.…”
Section: Stage 3 Analysesmentioning
confidence: 99%
“…Rutter [103] found that children hospitalized between six months of age and four years were more likely to have negative outcomes than those hospitalized prior to six months or after four years of age. Davidson and Smith [104] reported that among children receiving psychiatric care, those who had experienced an initial trauma prior to age ! 1 were three times as likely to develop psychiatric symptoms than those who had experienced the trauma during adolescence.…”
Section: Stage 3 Analysesmentioning
confidence: 99%
“…El médico responsable solicitó una evaluación por parte del Laboratorio de Neurofisiología Clínica donde se realizó una entrevista clínica a la paciente y se aplicó el cuestionario de experiencias traumáticas 5 . Se trata de un instrumento sencillo utilizado para el cribado de pacientes con trastorno por estrés postraumático que consta de tres partes diferenciadas: a) listado de experiencias traumáticas (18 ítems que investigan la existencia o no de experiencias traumáticas a lo largo de la vida y en caso afirmativo la edad a que sucedió y la duración), b) acontecimiento traumático que más preocupa en el momento actual con 9 ítems que investigan el acontecimiento estresante según los criterios diagnósticos del apartado A del DSM-IV y c) listado de síntomas que consta de 18 ítems que exploran los criterios B-D del DSM-IV.…”
Section: Presentación Del Casounclassified
“…Setenta y un pacientes con psicosis completaron una escala de experiencias disociativas (DES-II, Carlson y Putnam, 1993), un cuestionario de traumas (TQ, Davidson, Hughes y Blazer, 1990) y se les administró también los ítems de delirios y alucinaciones de la PANSS (Kay, Opler y Lindenmayer, 1988). Los resultados mostraron que los sujetos que presentaban alucinaciones y delirios habían experimentado un número significativamente mayor de las experiencias traumáticas en la infancia, pero no en la edad adulta.…”
Section: Introductionunclassified
“…Seventy-one patients with psychosis filled in a dissociative experiences scale (DES-II, Carlson & Putnam, 1993), a trauma questionnaire (TQ, Davidson, Hughes, & Blazer, 1990) and the PANSS delusion and hallucination items (Kay, Opler, & Lindenmayer, 1988). The results showed that subjects who had hallucinations and delusions had undergone a significantly larger number of traumatic experiences in childhood, but not as adults.…”
Section: Introductionmentioning
confidence: 99%